Descriptive chemistry of the elements - Brady, James E.; Holum, John R. ([S.l.] : Wiley, 1996)
Offers accurate, lucid, and interesting explanations of basic concepts and facts of chemistry, while helping readers develop skills in analytical thinking and problems solving.
Keywords: chemistry